HIV-1 replication activates CD4+ T cells with specificities for persistent herpes viruses - Haas, Anna; Rehr, Manuela; Graw, Frederik; Rusert, Peter; Bossart, Walter; Kuster, Herbert; Trkola, Alexandra; Guenthard, Huldrych F.; Oxenius, Annette (Embo Molecular Medicine, 2010)
Hyperactivation of CD4+ T cells is a hallmark of untreated HIV-1 infection. The antigenic specificities of activated CD4+ T cells and the underlying mechanisms leading to their activation remain thus far elusive. We report here that during HIV rebound the dynamics of HIV-specific CD4 + T cells is highly correlated with the dynamics of CD4+ T cells specific for persistent antigens derived from various members of the herpes virus family, whereas CD4 responses towards nonpersistent antigens were unaffected by HIV replication. Notably, the dynamics of HIV and herpes viral antigen-specific CD4+ T cells responses correlated with the expression level of activation markers on dendritic cells (DCs) and activated DCs were more potent in restimulating memory T cells. These data strongly suggest that HIV replication costimulates activation of CD4+ T cells specific for persistent herpes viral antigens via activation of DCs. We propose that a large proportion of activated T cells during untreated HIV infection may be specific for herpes viral antigens and identify a novel mechanism contributing to chronic immune activation in untreated HIV-1 infection. © 2010 EMBO Molecular Medicine.
CRIS-Team Scopus Importer:2022-12-14
Keywords: CD4+ T cells; Chronic immune activation; Dendritic cells; Herpes viruses; HIV pathogenesis